A study on improvement local waterworks business with public private partnership(PPP) - Kim, Hoyoung (KDI School, 2018)
This research paper aims to suggest a public-private partnership(PPP) scheme for local government to improve aged water supply pipe lines in local waterworks business. In 2015, 691 million tons of tap water was lost by leakage of aged water supply pipes and in terms of money, it was 60.6 billion won loss. The water flow rate, showing how much proportion of supplied tap water turns to revenue without loss while transmitting water through the pipe line is much lower in small sized cities than metropolitan cities. Though low water flow rate is continuing problems to local governments which take charge of local waterworks business, deteriorated waterworks networks has not been improved due to poor financial condition and low expertise in local governments which is identified as main factors to affect low water flow rate among other variables In this respect, PPP prescribed in Private Invest Act, would be good scheme to improve local waterworks by attracting private capital and advanced technologies into local waterworks business. Especially BTL is considered to be advantageous way in terms of inelastic demand of water and stability for investors. Finally, central government should reform subsidy policy as stopgap measure, and attract voluntary participation in sustainable development of local waterworks business from local governments.
Thesis(Master) --KDI School:Master of Public Management,2018.